Unravelling staphylococcal small-colony variants in cardiac implantable electronic device infections: clinical characteristics, management, and genomic insights - Liu, Si; Chen, Hongbin; Xu, Fangjie; Chen, Fengning; Yin, Yuyao; Zhang, Xiaoyang; Tu, Shangyu; Wang, Hui (Frontiers in Cellular and Infection Microbiology, 2024)
Objectives Staphylococcal small-colony variants (SCVs) are common in cardiac implantable electronic device (CIED) infections. This is the first retrospective and multi-case study on CIED infections due to staphylococcal SCVs, aiming to provide a theoretical basis for the clinical management of CIED and device-related infections caused by staphylococcal SCVs. Methods Ninety patients with culture positive CIED infections were enrolled between 2021 and 2022. We compared the demographic and clinical characteristics of patients with and without SCVs and performed genomic studies on SCVs isolates. Results Compared to patients without SCVs, those with SCVs had a longer primary pacemaker implantation time and were more likely to have a history of device replacement and infection. They showed upregulated inflammatory indicators, especially higher NEUT% (52.6 vs. 26.8%, P = 0.032) and they had longer hospital stays (median 13 vs. 12 days, P = 0.012). Comparative genomics analysis was performed on Staphylococcus epidermidis wild-type and SCVs. Some genes were identified, including aap, genes encoding adhesin, CHAP domain-containing protein, LPXTG cell wall anchor domain-containing protein, and YSIRK-type signal peptide-containing protein. Conclusion Staphylococcal SCVs affect the clinical characteristics of CIED infections. The process of staphylococcal SCVs adherence, biofilm formation, and interaction with neutrophils play a vital role.